2019
DOI: 10.1177/1120700019834793
|View full text |Cite
|
Sign up to set email alerts
|

Heart transplant secondary to cobalt toxicity after hip arthroplasty revision

Abstract: Introduction: Cobalt toxicity in patients with hip arthroplasty is a rare complication, but it should be considered in those patients who, after a ceramic fracture, were implanted with a metal-on-polyethylene prosthesis. The complete removal of ceramic particles during revision surgery can be complicated. If the bearing surface is replaced with a metalon-polyethylene prosthesis, these residual ceramic particles may wear down the chrome-cobalt head, producing localised metallosis. This can trigger blood metal i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 9 publications
0
14
0
Order By: Relevance
“…Previous studies have reported many cases of CVD caused by a cobalt poisoning dose, and suggested that THA patients with higher doses of cobalt presented with more severe CVD (Dahms et al 2014;Fox et al 2016;Samar et al 2015;Sanz Pérez et al 2019). Due to a lack of data about a possible association between cobalt and CVD in the general population, our research aimed to ll this knowledge gap.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have reported many cases of CVD caused by a cobalt poisoning dose, and suggested that THA patients with higher doses of cobalt presented with more severe CVD (Dahms et al 2014;Fox et al 2016;Samar et al 2015;Sanz Pérez et al 2019). Due to a lack of data about a possible association between cobalt and CVD in the general population, our research aimed to ll this knowledge gap.…”
Section: Discussionmentioning
confidence: 99%
“…Case studies of severe cardiomyopathy have revealed the association between poisoning cobalt doses and CVD due to the increased use of metal-to-metal (MoM) hip implants in patients undergoing total hip arthroplasty (THA) (Choi et al 2019;Sanz Pérez et al 2019). The blood cobalt levels of these patients could reach a fatal dose, as high as 641.6 μg/L (Dahms et al 2014;Fox et al 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a clear requirement for future experimental study design to take a more focused approach with stringent inclusion/exclusion criteria around cobalt levels being considered. Elevated cobalt at levels over 250 µg/l have been shown to be a risk factor for developing systemic complications, 5 and published case reports document cardiac transplantation 43 , 45 , 48 , 53 , 54 and death 46 , 51 , 52 , 55 , 59 in patients with severely elevated blood cobalt ions. Currently it is unclear whether there is a hard cut-off value and cardiac dysfunction may occur at cobalt levels less than 250 µg/l ( Table II ).…”
Section: Discussionmentioning
confidence: 99%
“… 52 Echocardiographs most commonly demonstrated a decreased left ventricular ejection fraction 42 , 43 , 45 - 47 , 49 - 51 , 53 , 57 - 59 , 61 but also a dilated atrium, 42 diastolic dysfunction, 39 - 41 , 47 left ventricular hypertrophy, 53 , 56 , 62 and a pericardial effusion. 52 , 53 Outcomes have varied from full recovery after revision surgery 39 - 42 , 44 , 47 , 53 , 56 , 58 , 60 or chelation therapy, 53 , 57 , 61 , 62 to left ventricular assist device implantation, 49 , 50 to cardiac transplantation 43 , 45 , 48 , 53 , 54 or death. 46 , 51 , 52 , 55 , 56 , 58 …”
Section: Introductionmentioning
confidence: 99%